Pembuatan Website Untuk Membantu Pemasaran Produk Batik Tulis Dan Ecoprint Pada Umkm Lemayung Di Kelurahan Kepanjenlor Kota Blitar - Nurul Azmy; Arief Bachtiar; Kiky Asmara (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
MSMEs or Micro, Small and Medium Enterprises are businesses owned by persons or legal entities that meet the requirements to be classified as a business. Lemayung is an MSME that sells various kinds of batik products and ecoprints located in KepanjenLor Village, Blitar City. In this community service activity, there is a work program that focuses on utilizing digital marketing. One of the aspects emphasized in this work program is the creation of a website for Lemayung SMEs. It is hoped that this can expand market reach and increase sales of Lemayung MSMEs.